Third-Party Risk in the Availability Payment: The Palapa Ring Western Package (Journal of Indonesian Legal Studies, 2022)
The Palapa Ring Western Package is the first Public Private Partnership infrastructure project in Indonesia implementing Availability Payment (AP). Prevailing regulations allow the Government Contracting Agency (GCA) and Implementing Business Entity (IBE) to determine the system of incentives and penalties of AP in their project contract. This research explores two main issues: (1) whether the IBE has obligation for contingent cost liabilities outside of the contractually determined AP amount in the occurrence of damage caused by a third party which interrupts or disrupts infrastructure service availability and (2) whether the GCA has the right to penalize AP amount to the IBE in the occurrence of damage by a third party which interrupts or disrupts service availability. By applying normative legal research using the statute approach, this research concludes that in this project, the IBE has obligation for contingent cost liabilities outside of contractually determined AP amount in the occurrence of damage by a third party and the GCA has the right to penalize AP amount if the IBE fails to maintain service availability. The contractual allocation of operational and maintenance risk to the IBE creates obligation to bear costs during the project lifetime including those due to third-party risk. Further, the use of formula to calculate AP to IBE is solely based on performance data in maintaining service availability according to contractually agreed standards. Thus, the use of AP in the Palapa Ring Western Package may be a point to reference for future Public Private Partnership infrastructure projects.